2022
DOI: 10.1136/bmjinnov-2021-000879
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ehteraz digital contact tracing app versus conventional contact tracing in managing the outbreak of COVID-19 in the State of Qatar

Abstract: IntroductionContact tracing is an integral component of the overall public health strategy for controlling the outbreak of infectious diseases such as COVID-19. In addition to the conventional contact tracing, Qatar has implemented Ehteraz, a proximity-tracing mobile phone App using global positioning system and Bluetooth technologies. In this paper, we aim to evaluate the accuracy of Ehteraz as a contact tracing App based on the WHO contact tracing criteria and compare its effectiveness to the traditional hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In addition to serious privacy issues, DCTAs have caused many other inconveniences, such as incorrect tracking and problems affecting the normal use of mobile phones [8,21]. Studies have shown that many of the close contacts located by a DCTA did not have any contact with COVID-19 patients, but they were also wrongly traced and isolated [8,22]. The operation of a DCTA has also been shown to affect the users' normal use of their cell phones, such as reducing the phone's running speed and affecting its battery life [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serious privacy issues, DCTAs have caused many other inconveniences, such as incorrect tracking and problems affecting the normal use of mobile phones [8,21]. Studies have shown that many of the close contacts located by a DCTA did not have any contact with COVID-19 patients, but they were also wrongly traced and isolated [8,22]. The operation of a DCTA has also been shown to affect the users' normal use of their cell phones, such as reducing the phone's running speed and affecting its battery life [21].…”
Section: Introductionmentioning
confidence: 99%